2018
DOI: 10.3389/fpsyt.2018.00568
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Magnetoencephalographic Interictal Epileptiform Discharge and Cognitive Function in Young Children With Typical Development and With Autism Spectrum Disorders

Abstract: Electroencephalograms of individuals with autism spectrum disorders (ASD) show higher rates of interictal epileptiform discharges (IEDs), which are known to have an inverse association with cognitive function in typically developed (TD) children. Nevertheless, that phenomenon has not been investigated adequately in children with ASD. From university and affiliated hospitals, 163 TD children (84 male, 79 female, aged 32–89 months) and 107 children (85 male, 22 female, aged 36–98 months) with ASD without clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…Few studies have analyzed the association between IEDs and ASD. The studies of Tetsu [30] and Milovanovic [75], which do not support an association between ASD and IED, are recent studies that present statistical significance. Few studies have reported clinical relevance [30,75].…”
Section: Future Research Directions and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have analyzed the association between IEDs and ASD. The studies of Tetsu [30] and Milovanovic [75], which do not support an association between ASD and IED, are recent studies that present statistical significance. Few studies have reported clinical relevance [30,75].…”
Section: Future Research Directions and Conclusionmentioning
confidence: 99%
“…In this way, treatment providers seek to minimize and prevent negative outcomes and to increasingly stimulate these children earlier and to a greater extent because, despite revealing a permanent problem, which is neither linear nor insurmountable, these children are receptive to treatment. Thus, the purpose of ASD treatment is to achieve a good level of social and mental functioning using various approaches, including educational or behavioral, psychotherapeutic, or psychopharmacological therapies [30,31,32,33].…”
Section: Autistic Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Reddy and colleagues (Reddy, Younus, Sridhar & Reddy, 2019) found that epilepsy as one of the most complex brain disorders was associated with spontaneous damage as a result of abnormal electrical discharge in the brain and that about 40% of children diagnosed with epilepsy appear to have lesions that cannot be treated with antiepileptic drugs. In cases when generalized and partialtype epilepsy are associated with symptoms of synaptic failure (Joy & Fields, 2019), neurological damage, or manifestation characterized by a hyperexcitability of indefinite duration (Hirosawa, Kikuchi, Fukai, Hino & Kitamura et al, 2018), it may lead to a clinical manifestation of the chronic stage (Kynast, Lampe, Luck, Frisch & Arelin et al, 2018). According to Reddy the variety of antiepileptic drugs, however, does not help a part of epileptic patients (Izadi, Ondek, Schedlbauer, Keselman, Shahlaie & Gurkoff, 2018) who present a form of epilepsy which fails to be fully traced in its clinical symptomatology based on the type of damage it causes (Reilly, Atkinson, Memon, Jones & Dabydeen et al, 2018) and the area in which it lies in the brain (Jones, Asato, Brown, Doss & Felton et al, 2020;Burke, Naseh, Rodriguez, Burgess & Loewenstein, 2019;Noebels, 2015).…”
Section: Introductionmentioning
confidence: 99%